House insulation: Perceived needs and willingness in Central Asia - Burulcha Sulaimanova; Dina Azhgaliyeva; Hans Holzhacker (Asian Development Bank Institute (ADBI), 2024)
This research aims to assess Central Asian households' willingness to insulate their homes and the factors influencing this decision by utilizing Central Asia Regional Economic Cooperation (CAREC) Institute data from the "Household Access to Energy in The Fergana Valley" survey, which was conducted in 2023. This study addresses key research questions regarding household decision-making processes and the impact of energy-saving behavior. The empirical findings reveal key factors influencing household insulation decisions. Urban residence negatively affects insulation decisions, indicating that such decisions are more likely to be made in rural than in urban areas. Older household heads are less likely to undertake insulation measures, while construction materials and heating sources significantly influence insulation decisions. Additionally, the energy-saving behavior index positively influences insulation decisions, indicating the potential for promoting energysaving practices to encourage broader adoption of insulation measures. Given these empirical findings, the policy recommendations include developing tailored interventions to promote insulation practices for vulnerable groups with greater needs and willingness to insulate. These groups include rural households, those with higher heating expenditures, those using solid or fossil fuels for heating, and low- to middle-income households.
Keywords: Q4; Q5; R2; R3; 330; heating; building retrofit; environmental awareness; fossil fuel; climate change mitigation; Central Asia